Feeding guild of non‐host community members affects host‐foraging efficiency of a parasitic wasp. Issue 6 (1st June 2016) - de Rijk, Marjolein; Yang, Daowei; Engel, Bas; Dicke, Marcel; Poelman, Erik H.
Abstract: Interactions between predator and prey, or parasitoid and host, are shaped by trait‐ and density‐mediated processes involving other community members. Parasitoids that lay their eggs in herbivorous insects locate their hosts through infochemicals such as herbivore‐induced plant volatiles (HIPVs) and host‐produced kairomones. Hosts are frequently accompanied by non‐host herbivores that are unsuitable for the parasitoid. These non‐hosts may interfere with host location primarily through trait‐mediated processes, by their own infochemicals, and their induction of the emission of plant volatiles. Although it is known that single non‐hosts can interfere with parasitoid host location, it is still unknown whether the observed effects are due to species specific characteristics or to the feeding habits of the non‐host herbivores. Here we addressed whether the feeding guild of non‐host herbivores differentially affects foraging of the parasitoid Cotesia glomerata for its common host, caterpillars of Pieris brassicae feeding on Brassica oleracea plants. We used different phloem‐feeding and leaf‐chewing non‐hosts to study their effects on host location by the parasitoid when searching for host‐infested plants based on HIPVs and when searching for hosts on the plant using infochemicals. To evaluate the ultimate effect of these two phases in host location, we studied parasitism efficiency of parasitoids in small plant communities under field‐tent conditions. We show that leaf‐chewing non‐hosts primarily affected host location through trait‐mediated effects via plant volatiles, whereas phloem‐feeding non‐hosts exerted trait‐mediated effects by affecting foraging efficiency of the parasitoid on the plant. These trait‐mediated effects resulted in associational susceptibility of hosts in environments with phloem feeders and associational resistance in environments with non‐host leaf chewers.